Influence of perceived remuneration and performance self-appraisal on work motivation among bank employees in Ibadan metropolis, Nigeria - Philip Adekanmbi, Foluso; I Ukpere, Wilfred; O Adegoke, Steve (International Journal of Psychosocial Rehabilitation, 2024)
The purpose of the present paper is to examine the influence of perceived remuneration and performance self-appraisal on work motivation among bank employees in Ibadan metropolis, Nigeria. Therefore, this paper plans to suggest ways of increasing employees work motivation within the Nigerian banking industry, especially banks in Oyo State. The current investigation adopted a quantitative research approach as well as a cross-sectional survey research design. The empirical findings showed that although both perceived remuneration and performance self-appraisal jointly predict work motivation among the bank employees in Ibadan metropolis, Nigeria, only perceived remuneration was found to have a significant influence on work motivation among the bank employees in Ibadan metropolis, Nigeria. Also, the research showed that among the three demographic factors (sex, educational qualification, and religion) that significantly jointly influence work motivation among bank employees in Ibadan metropolis (Nigeria), only educational qualification showed a significant independent (main) influence on work motivation. Furthermore, this paper concluded that the Nigerian bank employees perception of the remuneration system under which they work is a factor of how old they are and how much work experience they have, and that their work motivation increases with a favorable perception of their remuneration system. In addition, the present study has shown that the Nigerian bank employee's age leads to an increase in their work experience.Consequently, these findings have major implications for good human relationships, positive employee behavior management, employee motivation, as well as economic growth and excellent job performance within the Nigerian banking industry.